Method for preparing pyruvic acid from polylactic acid waste plastics through series hydrolysis and oxidation

By using cerium indium composite metal oxide catalyst and alkaline solvent in polylactic acid waste plastics, polylactic acid is successfully converted into valuable small-molecular chemicals such as pyruvate, solving the problem of polylactic acid waste treatment and achieving an efficient and green upgrade cycle.

CN119798064APending Publication Date: 2025-04-11NANJING TECH UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411693250.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively process and recycle polylactic acid waste, and the traditional upgrade recycling methods have problems such as high pressure hydrogen demand and difficult separation of by-products.

Method used

The cerium-indium composite metal oxide was used as the catalyst support and the tandem hydrolysis and oxidation reaction of polylactic acid was carried out in combination with an alkaline solvent, which successfully converted the polylactic acid into pyruvate, lactic acid and acetic acid, and the yield of pyruvate reached 86.7%.

Benefits of technology

Polylactic acid degradation with high degradation rate, mild degradation conditions and high selectivity has been achieved. The generated pyruvate has a high yield and is suitable for industrial applications, achieving the goal of green upgrading and circulation of waste plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798064A_ABST
    Figure CN119798064A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing pyruvic acid by polylactic acid waste plastics through series hydrolytic oxidation, which comprises the following steps: placing polylactic acid in an alkaline solvent, catalyzing PLA to perform series hydrolytic oxidation reaction through a catalyst, and completely converting polylactic acid into pyruvic acid, lactic acid and acetic acid; wherein pyruvic acid is a main product; wherein the carrier of the catalyst is a cerium-indium composite metal oxide, and the active component is one of ruthenium, platinum, palladium, cobalt and molybdenum. The method has the advantages of high efficiency, greenness, mild reaction conditions and the like, can efficiently catalyze hydrolysis and oxidation of PLA, has high industrial application value, and achieves the purpose of upgrading and recycling waste plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of recycling of waste plastics, and specifically relates to a method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics. Background Art

[0002] Currently, traditional polymers have received increasing attention due to their long-term impact on the environment. Therefore, it is particularly important to seek environmentally friendly alternative materials. Biodegradable polymers are considered to be eco-friendly materials because they can naturally degrade within a few months under specific conditions (such as industrial composting environments) and can be prepared using renewable resources. Polylactic acid (PLA), as a biodegradable polymer, has been widely used in agriculture, industry, and medicine due to its physical properties similar to existing synthetic plastics, and the market demand has continued to grow in recent years. However, the annual production of PLA has reached 900,000 tons, resulting in a large amount of waste that cannot be effectively treated or recycled. This is because the distribution of microorganisms that can degrade PLA is limited, and they can only degrade PLA with a molecular weight below 10.0 kDa. Therefore, it is crucial to develop new, innovative and green methods to convert waste plastic PLA into valuable small molecule chemicals.

[0003] In the context of circular economy principles for plastics innovation, various methods have been explored for the upgrading and recycling of polylactic acid materials. Traditional chemical processes, such as hydrolysis and alcoholysis, usually require large amounts of organic solvents and lead to the formation of oligomeric by-products that are difficult to separate. In contrast, catalytic hydrogenation has been proposed as an attractive strategy for upgrading and recycling polylactic acid. However, these methods have certain limitations, such as the need for high-pressure hydrogen and the possible production of by-products that are difficult to separate. Therefore, there is an urgent need to develop green, mild, and efficient methods for upgrading and recycling polylactic acid. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] The purpose of the present invention is to provide a method for producing pyruvic acid by degrading waste plastic polylactic acid with high degradation rate, mild degradation conditions and high selectivity.

[0007] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics, comprising:

[0008] Placing polylactic acid in an alkaline solvent, catalyzing the polylactic acid to undergo a tandem hydrolysis-oxidation reaction with a catalyst, and completely converting the polylactic acid into pyruvic acid, lactic acid and acetic acid; wherein pyruvic acid is the main product; specifically, the yield of pyruvic acid is not less than 40%; further, the yield of pyruvic acid is not less than 80%; optimally, the yield of pyruvic acid is as high as 86.7%;

[0009] The carrier of the catalyst is a cerium-indium composite metal oxide, and the active component is one of ruthenium, platinum, palladium, cobalt and molybdenum.

[0010] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the alkaline solvent is selected from one of lithium hydroxide, sodium hydroxide and potassium hydroxide.

[0011] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the alkaline solvent is lithium hydroxide.

[0012] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the concentration of the alkaline solvent is 0.1 mol / L to 0.5 mol / L.

[0013] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the concentration of the alkaline solvent is 0.2 mol / L.

[0014] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics of the present invention, the cerium-indium composite metal oxide is Ce3InO x .

[0015] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the active component is platinum, and the loading amount of the active component is 1 to 10 wt%.

[0016] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the active component is platinum, and the loading amount of the active component is 2 wt%.

[0017] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the mass ratio of the added amount of the catalyst to the polylactic acid is 0.08-0.2:0.1.

[0018] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the mass ratio of the added amount of the catalyst to the polylactic acid is 0.12:0.1.

[0019] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the serial hydrolysis and oxidation reaction is carried out in a high-purity oxygen atmosphere, the reaction pressure is 0.5-2 MPa, the reaction temperature is 150-180°C, and the reaction time is 15-120 min.

[0020] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the serial hydrolysis and oxidation reaction is carried out in a high-purity oxygen atmosphere, with a reaction pressure of 1 MPa, a reaction temperature of 160° C., and a reaction time of 30 min.

[0021] As a preferred embodiment of the method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics of the present invention, the serial hydrolysis and oxidation reaction specifically comprises the following steps:

[0022] (1) adding PLA, catalyst and alkaline solvent into a high temperature and high pressure reactor;

[0023] (2) Use high-purity oxygen to charge and discharge the reactor three times to exhaust the air in the reactor and fill the reactor with 0.5-2 MPa of O2;

[0024] (3) Raise the temperature in the reactor to 150-180°C at a heating rate of 5°C / min and maintain the reaction at this temperature for 15-120 min.

[0025] The reactor was cooled to room temperature, the reaction product was separated by centrifugal filtration, and the components and content of the liquid product were analyzed using high performance liquid chromatography (HPLC).

[0026] Another object of the present invention is to provide a method for preparing the catalyst as described above, comprising:

[0027] Providing an aqueous solution of chloroplatinic acid;

[0028] Providing composite metal oxide powder;

[0029] The cerium-indium composite metal oxide powder and deionized water are fully mixed, and a chloroplatinic acid aqueous solution is slowly added dropwise under vigorous stirring, and the mixture is continuously stirred and immersed, and then the water is dried to obtain a solid product;

[0030] The obtained solid product is ground into powder, and the powder is calcined and reduced in a hydrogen-argon mixed gas to obtain a platinum-loaded cerium-indium composite metal oxide catalyst.

[0031] As a preferred embodiment of the method for preparing the catalyst of the present invention, the mass volume ratio of the metal oxide powder to chloroplatinic acid is 0.5 g:1.06-5.25 mL.

[0032] As a preferred embodiment of the method for preparing the catalyst of the present invention, the chloroplatinic acid aqueous solution is provided, anhydrous chloroplatinic acid is dissolved in deionized water, and the chloroplatinic acid aqueous solution is obtained by ultrasonication and shaking;

[0033] As a preferred embodiment of the preparation method of the catalyst of the present invention, the powder is calcined in a hydrogen-argon mixed gas at a temperature of 300 to 500° C. and a calcination time of 3 to 6 hours; the hydrogen content of the hydrogen-argon mixed gas is 10%, and the flow rate of the hydrogen-argon mixed gas is 80 mL / min.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The present invention proposes a method for preparing pyruvic acid using polylactic acid waste plastic as raw material, which has the advantages of high efficiency, greenness, mild reaction conditions, etc., can efficiently catalyze the hydrolysis and oxidation of polylactic acid, has strong industrial application value, and achieves the purpose of upgrading and recycling waste plastics.

[0036] 2. The present invention adopts a catalyst carrier of cerium-indium composite metal oxide, and active components such as ruthenium, platinum, palladium, cobalt, molybdenum, etc., which can completely convert polylactic acid into pyruvic acid, lactic acid and acetic acid with nearly 100% selectivity, providing a new application for the green degradation of waste plastics. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0038] Figure 1 The reaction device diagram in the present invention is

[0039] Figure 2 3, 11, 12 and 13 in Examples of the present invention.

[0040] Figure 3 1 is a graph of the reaction products and their yields at different lithium hydroxide dosages in Example 14 of the present invention.

[0041] Figure 4 1 is a graph of the reaction products and their yields at different times in Example 15 of the present invention. DETAILED DESCRIPTION

[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the present invention will be described in more detail below through embodiments.

[0043] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0044] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0045] Unless otherwise specified, the raw materials used in the examples were purchased commercially.

[0046] Example 1

[0047] 0.1 g PLA and 10 mL H2O were added to a 25 mL high temperature and high pressure reactor. The air in the reactor was discharged and charged with high purity O2 three times, and then 1 MPa O2 was charged. The temperature was raised to 160°C at a heating rate of 5°C / min and maintained for 30 min. The reactor was then cooled to room temperature. The product was centrifuged and filtered, and deionized water was added dropwise to make the volume 5 mL. The components and content of the liquid product were determined by HPLC. The products were mainly pyruvic acid, lactic acid, acetic acid and acrylic acid.

[0048] Example 2

[0049] 0.1 g PLA, 50 mg LiOH, and 10 mL H2O were added to a 25 mL high temperature and high pressure reactor. The air in the reactor was discharged and charged with high purity O2 three times, and then 1 MPa O2 was filled. The temperature was increased to 160°C at a heating rate of 5°C / min and maintained for 30 min. The reactor was then cooled to room temperature. The product was centrifuged and filtered, and deionized water was added dropwise to make the volume 5 mL. The components and content of the liquid product were determined by HPLC. The products were mainly pyruvic acid, lactic acid, acetic acid and acrylic acid.

[0050] Example 3

[0051] In the present invention, we use the same carrier cerium-indium composite metal oxide (Ce3InO x ), but through the optimization of the preparation method, a catalyst loaded with the active component Pt was successfully prepared, which makes our method more significantly advantageous in the preparation of pyruvic acid by tandem hydrolysis and oxidation of polylactic acid waste plastics.

[0052] Dissolve cerium nitrate hexahydrate and indium nitrate tetrahydrate in a molar ratio of 3:1 in 40 mL of deionized water and place in an ultrasonic cleaner for 10 minutes until the solid is completely dissolved. Add ammonia solution dropwise during stirring to produce precipitation, adjust the pH to 10-11, and then stir at room temperature for 30 minutes. Place in a reactor for hydrothermal treatment at 180°C for 12 hours, filter and wash, and then transfer to a 60°C oven for 12 hours to thoroughly dry the water. After taking out, grind the solid thoroughly, and after grinding, place the powder in a muffle furnace, heat to 500°C at a heating rate of 5°C / min, and calcine for 3 hours to obtain Ce3InO x powder.

[0053] Accurately weigh 0.5g Ce3InO x The carrier was placed in 25 mL of deionized water and stirred continuously. 2.14 mL of chloroplatinic acid solution was slowly dripped into the flask. After stirring at room temperature for 3 h, it was allowed to stand and then placed in an oven at 110 ° C for 12 h for drying. After being taken out, the solid powder was fully ground. After grinding, the powder was placed in a tube furnace, 10% H2 / Ar (80 mL / min) was introduced, and 400 ° C (5 ° C / min) was maintained for 4 h to obtain Pt / Ce3InO with a Pt loading of 2 wt.%. x catalyst.

[0054] 0.1g PLA, 0.12g 2% Pt / Ce3InO x , 10mL H2O was added to a 25mL high-temperature and high-pressure reactor, and the air in the reactor was discharged and filled with high-purity O2 three times to expel the air, and then 1MPa O2 was filled in. The temperature was raised to 160℃ at a heating rate of 5℃ / min and maintained for 30min. Then the reactor was cooled to room temperature. After the product was centrifuged and filtered, deionized water was added dropwise to make up to 5mL. The components and content of the liquid product were determined by HPLC. The products were mainly pyruvic acid, lactic acid, acetic acid and acrylic acid.

[0055] Example 4

[0056] 0.1 g PLA, 50 mg LiOH, 0.12 g 2% Pt / Ce3InO x , 10mL H2O was added to a 25mL high-temperature and high-pressure reactor, and the air in the reactor was discharged and filled with high-purity O2 three times to expel the air, and then 1MPa O2 was filled in. The temperature was raised to 160℃ at a heating rate of 5℃ / min and maintained for 30min. Then the reactor was cooled to room temperature. After the product was centrifuged and filtered, deionized water was added dropwise to make up to 5mL. The components and content of the liquid product were determined by HPLC. The products were mainly pyruvic acid, lactic acid, acetic acid and acrylic acid.

[0057] The test results of Examples 1 to 4 are shown in Table 1.

[0058] Table 1

[0059]

[0060] As shown in Table 1, the solubility of PLA is extremely low without the addition of catalyst and alkaline solvent. When only LiOH is present, PLA can be almost completely dissolved and converted into lactic acid. However, the addition of catalyst alone cannot promote the hydrolysis and oxidation of PLA. But when the catalyst coexists with the alkaline solvent LiOH, PLA can be completely dissolved, and the yield of conversion to pyruvic acid is 86.7%, highlighting the synergistic catalytic effect of catalyst and alkaline medium in the dissolution and conversion process of PLA.

[0061] Example 5

[0062] Dissolve 0.0209g RuCl3 in 10mL deionized water and place in an ultrasonic cleaner for 5 minutes, shaking continuously until the solid is completely dissolved. Accurately weigh 0.5g Ce3InO x The carrier (prepared in the same manner as in Example 3) was placed in 25 mL of deionized water and stirred continuously. Then, the RuCl3 aqueous solution was slowly dripped into the flask. After stirring at room temperature for 3 h, it was allowed to stand and then placed in an oven at 110°C for 12 h for drying. After being taken out, the solid powder was fully ground. After grinding, the powder was placed in a tube furnace, 10% H2 / Ar (80 mL / min) was introduced, and the temperature was maintained at 400°C (5°C / min) for 4 h to obtain Ru / Ce3InO with a Ru loading of 2 wt.%. x catalyst.

[0063] Example 6

[0064] Dissolve 0.01034 g Co(NO3)2·6H2O in 10 mL deionized water and place in an ultrasonic cleaner for 5 min, shaking continuously until the solid is completely dissolved. Accurately weigh 0.5 g Ce3InO x The carrier (prepared in the same way as in Example 3) was placed in 25 mL of deionized water and stirred continuously. Then, the aqueous solution of Co(NO3)2 was slowly dripped into the flask. After stirring at room temperature for 3 h, it was allowed to stand and then placed in an oven at 110°C for 12 h for drying. After being taken out, the solid powder was fully ground. After grinding, the powder was placed in a tube furnace, 10% H2 / Ar (80 mL / min) was introduced, and the temperature was kept at 400°C (5°C / min) for 4 h to obtain Co / Ce3InO with a Co loading of 2 wt.%. x catalyst.

[0065] Example 7

[0066] Dissolve 0.0208g (NH4)2MoO4 in 10mL deionized water and place in an ultrasonic cleaner for 5 minutes, shaking continuously until the solid is completely dissolved. Accurately weigh 0.5g Ce3InO x The carrier (prepared in the same manner as in Example 3) was placed in 25 mL of deionized water and stirred continuously. Then, the (NH4)2MoO4 aqueous solution was slowly dripped into the flask. After stirring at room temperature for 3 h, it was allowed to stand and then placed in an oven at 110°C for 12 h for drying. After being taken out, the solid powder was fully ground. After grinding, the powder was placed in a tube furnace, 10% H2 / Ar (80 mL / min) was introduced, and the temperature was maintained at 400°C (5°C / min) for 4 h to obtain Mo / Ce3InO with a Mo loading of 2 wt.%. x catalyst.

[0067] Example 8

[0068] Accurately weigh 0.5g Ce3InO x The carrier was placed in 25 mL of deionized water and stirred continuously. 9.62 mL of chloropalladic acid solution (10 mM) was slowly dripped into the flask. After stirring at room temperature for 3 h, it was allowed to stand and then placed in an oven at 110 ° C for 12 h for drying. After being taken out, the solid powder was fully ground. After grinding, the powder was placed in a tube furnace, 10% H2 / Ar (80 mL / min) was introduced, and 400 ° C (5 ° C / min) was maintained for 2 h to obtain Pd / Ce3InO with a Pd loading of 2 wt.%. x catalyst.

[0069] The catalysts obtained in Examples 5 to 8 were used to catalyze the serial hydrolysis and oxidation of polylactic acid to prepare pyruvic acid, and the specific method was:

[0070] 0.12g of catalyst, 0.1g of PLA, 50mg of LiOH, and 10mL of H2O were added to a 25mL high-temperature and high-pressure reactor. High-purity O2 was charged and discharged three times to exhaust the air in the reactor, and then 1MPa of O2 was charged. The temperature was raised to 160°C at a heating rate of 5°C / min and maintained for 30 minutes. The reactor was cooled to room temperature. After the product was centrifuged and filtered, deionized water was added dropwise to make the volume 5mL. The components and content of the liquid product were determined by HPLC. The products were mainly pyruvic acid, lactic acid, acetic acid, and acrylic acid. The test results are shown in Table 2.

[0071] Table 2

[0072]

[0073] As shown in Table 2, the bimetallic composite oxides loaded with different active components have a certain influence on the product yield of the tandem hydrolysis and oxidation of polylactic acid. It can be seen that metal Pt has excellent activity for the tandem oxidative hydrolysis of polylactic acid.

[0074] Example 9

[0075] 0.1g PLA, 50mg NaOH, 0.12g 2% Pt / Ce3InO x , 10mL H2O was added to a 25mL high-temperature and high-pressure reactor, and the air in the reactor was discharged and filled with high-purity O2 three times to expel the air, and then 1MPa O2 was filled in. The temperature was raised to 160℃ at a heating rate of 5℃ / min and maintained for 30min. Then the reactor was cooled to room temperature. After the product was centrifuged and filtered, deionized water was added dropwise to make up to 5mL. The components and content of the liquid product were determined by HPLC. The products were mainly pyruvic acid, lactic acid, acetic acid and acrylic acid.

[0076] Example 10

[0077] 0.1g PLA, 50mg KOH, 0.12g 2% Pt / Ce3InO x , 10mL H2O was added to a 25mL high-temperature and high-pressure reactor, and the air in the reactor was discharged and filled with high-purity O2 three times to expel the air, and then 1MPa O2 was filled in. The temperature was raised to 160℃ at a heating rate of 5℃ / min and maintained for 30min. Then the reactor was cooled to room temperature. After the product was centrifuged and filtered, deionized water was added dropwise to make up to 5mL. The components and content of the liquid product were determined by HPLC. The products were mainly pyruvic acid, lactic acid, acetic acid and acrylic acid.

[0078] The test results of Examples 9 and 10 are shown in Table 3.

[0079] Table 3

[0080]

[0081]

[0082] As can be seen from Table 3, the data clearly show the effect of the addition of alkaline solvents on the yield of the products of the PLA tandem hydrolysis-oxidation reaction. The results show that as the alkalinity of the alkaline solvent increases, the yield of pyruvic acid shows a downward trend, while the yield of acetic acid increases accordingly. This phenomenon may be related to the pH adjustment ability of the alkaline solvent and its regulatory effect on the PLA hydrolysis pathway. Specifically, stronger alkaline conditions may promote the conversion of PLA to acetic acid and inhibit the conversion path to pyruvic acid. These findings provide important guidance for optimizing the hydrolysis-oxidation process of PLA and emphasize the key role of alkaline solvent selection in regulating product distribution.

[0083] Embodiment 11

[0084] Accurately weigh 0.5g Ce3InO x The carrier was placed in 25 mL of deionized water and stirred continuously. 1.06 mL of chloroplatinic acid solution was slowly dripped into the flask. After stirring at room temperature for 3 h, it was allowed to stand and then placed in an oven at 110 ° C for 12 h for drying. After being taken out, the solid powder was fully ground. After grinding, the powder was placed in a tube furnace, 10% H2 / Ar (80 mL / min) was introduced, and 400 ° C (5 ° C / min) was maintained for 4 h to obtain Pt / Ce3InO with a Pt loading of 1 wt.%. x catalyst.

[0085] Example 12

[0086] Accurately weigh 0.5g Ce3InO x The carrier was placed in 25 mL of deionized water and stirred continuously. 3.24 mL of chloroplatinic acid solution was slowly dripped into the flask. After stirring at room temperature for 3 h, it was allowed to stand and then placed in an oven at 110 ° C for 12 h for drying. After being taken out, the solid powder was fully ground. After grinding, the powder was placed in a tube furnace, 10% H2 / Ar (80 mL / min) was introduced, and 400 ° C (5 ° C / min) was maintained for 4 h to obtain Pt / Ce3InO with a Pt loading of 3 wt.%. x catalyst.

[0087] Embodiment 13

[0088] Accurately weigh 0.5g Ce3InO x The carrier was placed in 25 mL of deionized water and stirred continuously. 5.52 mL of chloroplatinic acid solution was slowly dripped into the flask. After stirring at room temperature for 3 h, it was allowed to stand and then placed in an oven at 110 ° C for 12 h for drying. After being taken out, the solid powder was fully ground. After grinding, the powder was placed in a tube furnace, 10% H2 / Ar (80 mL / min) was introduced, and 400 ° C (5 ° C / min) was maintained for 4 h to obtain Pt / Ce3InO with a Pt loading of 5 wt.%. x catalyst.

[0089] Pt / Ce3InO with different loading contents x The XRD patterns of the catalysts are Figure 1 As shown in the figure, it can be seen that after loading Pt, no characteristic diffraction peak of Pt appears, indicating that Pt is highly dispersed in Ce3InO x According to the test method in Examples 1 to 5, the Pt / Ce3InO xThe catalyst was used to catalyze the PLA tandem hydrolysis and oxidation reaction to produce alanine. The components and contents of the liquid products were determined by HPLC, and the products were mainly pyruvic acid, lactic acid, acetic acid and acrylic acid. The test results are shown in Table 4.

[0090] Table 4

[0091]

[0092] From the data in Table 4, we can see that Pt / Ce3InO x The catalyst showed excellent catalytic activity for the hydrolysis and oxidation of polylactic acid. Secondly, with the increase of Pt loading, the yield of pyruvic acid increased rapidly and then decreased, indicating that the best catalytic effect can be achieved when the loading amount of the active component Pt is 2%.

[0093] Embodiment 14

[0094] 0.1g PLA, 0.12g 2% Pt / Ce3InO x , 10mL H2O, 20mg, 30mg, 40mg, 50mg, 80mgLiOH were added to a 25mL high temperature and high pressure reactor respectively, and the air in the reactor was discharged and filled with high purity O2 three times to exhaust the air, and then filled with 1MPa O2, and the temperature was raised to 160℃ at a heating rate of 5℃ / min, and kept for 30min, and then the reactor was cooled to room temperature, and the product was centrifuged and filtered, and deionized water was added dropwise to make the volume 5mL, and the liquid product components and content were determined by HPLC. The products were mainly pyruvic acid, lactic acid, acetic acid and acrylic acid. The test results are as follows Figure 3 shown.

[0095] The amount of lithium hydroxide was screened. Figure 3 It can be seen that without adding lithium hydroxide, polylactic acid hardly reacts. As the amount of lithium hydroxide increases, the yield of pyruvic acid also increases. The experimental results show that when the amount of lithium hydroxide is accurately controlled at 0.05g, the yield of pyruvic acid reaches a maximum value of 86.7%. However, when the amount of lithium hydroxide exceeds 0.05g, the yield of pyruvic acid shows a downward trend.

[0096] Embodiment 15

[0097] 0.1 g PLA, 50 mg LiOH, 0.12 g 2% Pt / Ce3InO x, 10mL H2O was added to a 25mL high temperature and high pressure reactor, and the air in the reactor was discharged and filled with high purity O2 three times to exhaust the air, and then filled with 1MPa O2, and the temperature was raised to 160℃ at a heating rate of 5℃ / min, and maintained for 15min, 20min, 25min, 30min, and 60min respectively, and then the reactor was cooled to room temperature, and the product was centrifuged and filtered, and deionized water was added dropwise to make the volume 5mL, and the liquid product components and content were determined by HPLC. The products were mainly pyruvic acid, lactic acid, acetic acid and acrylic acid. The test results are as follows Figure 4 shown.

[0098] Depend on Figure 4 It can be seen that in the polylactic acid tandem hydrolysis and oxidation reaction, the catalytic effect first increases and then weakens as time goes by. The present invention provides a new method that exhibits excellent performance in the reaction, especially as the reaction time increases, the output of pyruvic acid increases significantly. This discovery provides a new perspective for the efficient conversion of polylactic acid plastic waste and may have an important impact on the production of sustainable chemicals. The present invention can optimize the polylactic acid tandem hydrolysis and oxidation process by adding alkaline solvents and catalysts, thereby accelerating the degradation rate and increasing the yield of the product. In addition, the catalyst is heterogeneous, the binding ability between the active components of the catalyst and the carrier is strong, it is not easy to lose during the reaction, the obtained product is easy to separate from the catalyst, the recovered catalyst can be recycled, and the recycled activity is high, so it is suitable for industrial production.

[0099] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics, characterized in that: include, Placing polylactic acid in an alkaline solvent, catalyzing the polylactic acid to undergo a series of hydrolysis and oxidation reactions with a catalyst, and completely converting the polylactic acid into pyruvic acid, lactic acid and acetic acid, wherein pyruvic acid is the main product; The carrier of the catalyst is a cerium-indium composite metal oxide, and the active component is one of ruthenium, platinum, palladium, cobalt and molybdenum.

2. The method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics according to claim 1, characterized in that: The alkaline solvent is selected from one of lithium hydroxide, sodium hydroxide and potassium hydroxide.

3. The method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics according to claim 2, characterized in that: The alkaline solvent is lithium hydroxide.

4. The method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics according to any one of claims 1 to 3, characterized in that: The concentration of the alkaline solvent is 0.1 mol / L to 0.5 mol / L.

5. The method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics according to claim 4, characterized in that: The cerium-indium composite metal oxide is Ce3InO x .

6. The method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics according to claim 5, characterized in that: The active component is platinum, and the loading amount of the active component is 1-10 wt %.

7. The method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics according to claim 6, characterized in that: The active component is platinum, and the loading amount of the active component is 2 wt %.

8. The method for preparing pyruvic acid by serial hydrolysis and oxidation of waste polylactic acid plastics according to any one of claims 5 to 7, characterized in that: The mass ratio of the added amount of the catalyst to the polylactic acid is 0.08-0.2:0.

1.

9. The method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics according to claim 8, characterized in that: The tandem hydrolysis-oxidation reaction is carried out in a high-purity oxygen atmosphere, with a reaction pressure of 0.5-2 MPa, a reaction temperature of 150-180° C., and a reaction time of 15-120 min.

10. The method for preparing pyruvic acid by serial hydrolysis and oxidation of polylactic acid waste plastics according to claim 9, characterized in that: The tandem hydrolysis-oxidation reaction has a reaction time of 30 minutes.

Citation Information

Patent Citations

  • Ruthenium-loaded metal oxide catalyst as well as preparation method and application thereof

    CN115121248A